Proteolytic processing of Alzheimer’s β-amyloid precursor protein - Zhang, Han (2011)
β–amyloid precursor protein (APP) is a critical factor in the pathogenesis of Alzheimer’s disease (AD). APP undergoes posttranslational proteolysis/processing to generate the hydrophobic β-amyloid (Aβ) peptides. Deposition of Aβ in the brain, forming oligomeric Aβ and plaques, is identified as one of the key pathological hallmarks of AD. The processing of APP to generate Aβ is executed by β- and γ-secretase and is highly regulated. Aβ toxicity can lead to synaptic dysfunction, neuronal cell death, impaired learning/memory and abnormal behaviors in AD models in vitro and in vivo. Aside from Aβ, proteolytic cleavages of APP can also give rise to the APP intracellular domain (AICD), reportedly involved in multiple types of cellular events such as gene transcription and apoptotic cell death. In addition to amyloidogenic processing, APP can also be cleaved by α-secretase to form a soluble or secreted APP ectodomain (sAPP-α) that has been shown to be mostly neuro-protective. In this review, we describe the mechanisms involved in APP metabolism and the likely functions of its various proteolytic products to give a better understanding of the patho/physiological functions of APP.